In silico molecular docking and in vitro antimicrobial efficacy of phytochemical compounds of Lantana camara Linn. - Anita, Adline; Selvaraj, D. (Current Botany, 2023)
The rise of multi-drug resistant bacteria and the extensive use of antibiotics has become a serious threat worldwide. The side effect of antibiotics swirled the researchers towards traditional medicine to find a therapeutic agent with antibacterial activity. The phytochemical compound from medicinal plants paves a way for the novel antibacterial agent. In the present study, in silico molecular docking of phytochemical compounds identified through GC-MS analysis and in vitro antibacterial efficacy of ethanolic leaf extract of Lantana camara were evaluated. In silico docking studies of 11 Phyto-ligands were carried out against 4 motifs- 1PHO, 5I5H, 5UW2 and 6NTW of Escherichia coli to estimate the binding energy and to know the protein-ligand interaction. Amongst all the phyto-ligands studied, 4,8,13-Cyclotetradecatriene-1,3-diol,1,5,9-trimethyl-12-(1-methylethyl) showed good affinity towards 1PHO, 4a(2H)-Phenanthrenecarboxaldehyde,1,3,4,9,10,10a-hexahydro-6-methoxy-1,1-dimethyl-7-(1-methylethyl) exhibited highest affinity with 5I5H motifs of E. coli, 4,8,13-Cyclotetradecatriene-1,3-diol, 1,5,9-trimethyl-12-(1-methylethyl) showed better affinity towards motif 5UW2 of E. coli and (Z)-4-Nitro-alpha-(p-nitrophenyl)cinnamic acid showed good affinity towards 6NTW motif of E. coli. The ethanolic leaf extract of L. camara L. showed concentration dependent activity against E. coli.